Implementasi Jurus Ak3+ Sebagai Upaya Kepedulian Terhadap Warga Yang Tertimpa Musibah - Supriyanto; Maksin, Mastina; Nasution, Hermawan (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the implementation of the Jurus ak3+ program in Probolinggo City as an innovation in public service that integrates death certificate issuance with direct financial assistance for bereaved families. A qualitative descriptive approach was employed, using data collection techniques such as in-depth interviews, observation, and documentation. The data were analyzed using David L. Weimer and Aidan R. Vining’s theory of policy implementation. The findings indicate that the implementation of Jurus ak3+ has been effective, fulfilling three key components of policy success: rational and contextual policy logic, supportive socio-institutional environment, and responsive implementer capacity. This program successfully addresses the real needs of economically vulnerable groups through timely, targeted, and socially impactful services. The study concludes that Jurus ak3+ is a best practice in vital event-based public policy implementation, effectively combining bureaucratic efficiency with social compassion in a sustainable and replicable model.